Foreign currency bank funding and global factors - Signe Krogstrup; Cédric Tille (Graduate Institute of International and Development Studies, 2018)
The literature on drivers of capital flows stresses the prominent role of global financial factors. Recent empirical work, however, highlights how this role varies across countries and time, and this heterogeneity is not well understood. We revisit this question by focusing on financial intermediaries' funding flows in different currencies. A portfolio model shows that the sign and magnitude of the response of foreign currency funding flows to global risk factors depend on the financial intermediary's pre-existing currency exposure. Analysis of data on European banks' aggregate balance sheets lends support to the model predictions, especially in countries outside the euro area.
Keywords: F32; F34; F36; 330; Currency mismatch; capital flows; push factors; spillovers; cross-border transmission of shocks; European bank balance sheets